Development aid: Regulatory Impact Assessment and conditionality. Issue 4 (1st October 2016) - Jakupec, Viktor; Kelly, Max
Abstract: The purpose of this paper is to examine how Regulatory Impact Assessment (RIA) can contribute to decision-making processes of Official Development Assistance (ODA) loans and grants. The point of departure for the discussion is the phenomenon that RIA, within a context of ODA, is applied by International Finance Institutions mainly in the context of Development Policy Loans, to introduce or strengthen country systems for Regulatory Impact Assessment. However, ODA grants, and loans, particularly when specific policy or regulatory conditions are attached to them, significantly impact economic and social conditions within the beneficiary country. This article examines what role RIA can play in facilitating a coherent decision-making process affecting the ODA allocation within a context of conditionalities requiring the introduction of new, or changes to existing, policies and regulations. The discussion considers the nexus between development aid effectiveness, conditionality and ownership, and RIA. The article argues a justification for applying RIA to ODA loans and grants which carry regulatory and policy conditionalities.